A Critique of the “Common Ownership of the Earth” Thesis - Abizadeh, Arash (Les ateliers de l'éthique / The Ethics Forum, 2013)
In On Global Justice, Mathias Risse claims that the earth’s original resources are collectively owned by all human beings in common, such that each individual has a moral right to use the original resources necessary for satisfying her basic needs. He also rejects the rival views that original resources are by nature owned by no one, owned by each human in equal shares, or owned and co-managed jointly by all humans. I argue that Risse’s arguments fail to establish a form of ownership at all and, moreover, that his arguments against the three rival views he considers all fall short. His argument establishes, rather, a moral constraint on any conventional system of property ownership.